378 Growing up Healthy in Ghana II: Socioeconomic and Spatial Predictors. (October 2012) - Reime, B; Hahn, A; Kreuels, B; Loag, W; Maiga, O; May, J
Abstract : Background and Aims: Especially in resource poor settings measures for health promotion should be guided by evidence to channel expenditures according to populations' health priorities. Our aim was to identify predictors for infants' health amenable for short or midterm change to guide health policy decision making in Ghana. Methods: This part of the Intermittent Preventive Treatment in Infants Trial used socioeconomic, behavioral and knowledge-related data that were collected on recruitment with interviews in the local language. Spatial data on the infants' residence area were measured by handheld global positioning system (GPS) receiver. We tested the association between these factors and health in bivariate and multivariable analyses adjusted for each other and for genetic and clinical factors. Results: In bivariate analyses, maternal age, financial status, TV, radio, refrigerator and kitchen in the house, malaria knowledge, effective protection against mosquitos and the villages' distance to the next hospital were related to health but birth order and water source were not. In multivariate analyses, infants from well-off families were twice as likely to grow up healthy (OR=2.03, 95%–CI=1.32–3.54) than infants from poor families. Type of mosquito protection and distance to hospital also were related to health. Conclusions: Independently of the child's genetic traits, effective protection against mosquitos and access to hospital may be related to better health outcomes in this area in Ghana. Further studies should explore how access to health services can be improved in remote settings. In the meantime, investment in effective mosquito protection may support growing up healthy in Ghana.